Effects of Mycorrhizal Colonization on Transcriptional Expression of the Responsive Factor JERF3 and Stress-Responsive Genes in Banana Plantlets in Response to Combined Biotic and Abiotic Stresses - Rashad, Younes M.; Fekry, Waleed M. E.; Sleem, Mohamed M.; Elazab, Nahla T. (Frontiers in Plant Science, 2021)
Banana plants (Musa acuminata L.) are exposed to various biotic and abiotic stresses that affect their production worldwide. Banana plants respond to these stresses, but their responses to combined stresses are unique and differ from those to various individual stresses. This study reported the effects of the mycorrhizal colonization of banana roots and/or infection with root rot on the transcriptional expression of the responsive factor JERF3 and stress-responsive genes (POD, PR1, CHI, and GLU) under different salinity levels. Different transcriptional levels were recorded in response to the individual, dual, or triple treatments. All the applied biotic and abiotic stresses triggered the transcriptional expression of the tested genes when individually applied, but they showed different influences varying from synergistic to antagonistic when applied in combinations. The salinity stress had the strongest effect when applied in combination with the biotic stress and/or mycorrhizal colonization, especially at high concentrations. Moreover, the salinity level differentially affects the banana responses under combined stresses and/or mycorrhizal colonization in addition, the mycorrhizal colonization of banana plantlets improved their growth, photosynthesis, and nutrient uptake, as well as greatly alleviated the detrimental effects of salt and infection stresses. In general, the obtained results indicated that the responses of banana plantlets under the combined stresses are more complicated and differed from those under the individual stresses depending on the crosstalks between the signaling pathways.